Interleukin-22 in Renal Protection and Its Pathological Role in Kidney Diseases - Ma, Qianqian; Luan, Jingyun; Bai, Yu; Xu, Caili; Liu, Fangyu; Chen, Bufeng; Ju, Dianwen; Xu, Hong (Frontiers in Immunology, 2022)
Chronic kidney injury has gradually become a worldwide public health problem currently affecting approximately 10% of the population, and can eventually progress to chronic end-stage renal disease characteristic by the result of epithelial atrophy. Interleukin-22 (IL-22) is a cytokine produced by activated immune cells, while acting mainly on epithelial cells ranging from innate immune response to tissue regeneration to maintain barrier integrity and promote wound healing. Accumulating data suggests that IL-22 has emerged as a fundamental mediator of epithelial homeostasis in the kidney through promoting tissue repair and regeneration, inhibiting oxidative stress, and producing antimicrobial peptides. Binding of IL-22 to its transmembrane receptor complex triggers janus kinase/tyrosine kinase 2 phosphorylation, which further activates a number of downstream cascades, including signal transducer and activator of transcription 3, MAP kinase, and protein kinase B, and initiates a wide array of downstream effects. However, the activation of the IL-22 signaling pathways promotes the activation of complement systems and enhances the infiltration of chemokines, which does harm to the kidney and may finally result in chronic renal failure of different autoimmune kidney diseases, including lupus nephritis, and IgA nephropathy. This review describes current knowledge of the basic features of IL-22, including structure, cellular origin and associated signaling pathways. Also we summarize the latest progress in understanding the physiological and pathological effects of IL-22 in the kidney, suggesting the potential strategies for the specific application of this cytokine in the treatment of kidney disease.